2020
DOI: 10.13106/jidb.2020.vol11.no2.41
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Technology Acceptance of Elderly living Alone in Smart City Environment: Based on AI Speaker

Abstract: This study is to examine the intention of the elderly who live alone in the customized AI speaker for the elderly living alone to improve the quality of life service for the elderly living alone in the smart city environment. Based on the quality of life model of the elderly, this study is applied to the technology acceptance model to investigate the relationship between perceived usefulness and ease of use on the sustained use intention. Research design, data and methodology: Residents in Suwon, Gyeonggi-do, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The results showed that perceived ease of use has a positive relationship with Jordanian users’ intention to adopt smart city technologies. This result is consistent with ( Gunabalan, Ooi & Yeap, 2022 ; Wang et al, 2022 ; Najdawi & Said, 2021 ; Yoo, Suh & Kim, 2020 ). As perceived ease of use is an essential construct in TAM, as it increases the acceptance and an ideal use of smart city technologies ( Tavitiyaman, Zhang & Tsang, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that perceived ease of use has a positive relationship with Jordanian users’ intention to adopt smart city technologies. This result is consistent with ( Gunabalan, Ooi & Yeap, 2022 ; Wang et al, 2022 ; Najdawi & Said, 2021 ; Yoo, Suh & Kim, 2020 ). As perceived ease of use is an essential construct in TAM, as it increases the acceptance and an ideal use of smart city technologies ( Tavitiyaman, Zhang & Tsang, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies determined that price value has no significant impact on BT adoption in different domains (Halassi et al. , 2019; Handoko and Lantu, 2021; Yoo and Park, 2019). These consequences specified that Chinese SC professionals believe that the use of BT is beneficial and valuable for them.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Alalwan (2020) confirmed that habit has a substantial role to build customers' continuous intention to use mobile commerce. Yoo and Park (2019) established the significant progressive impact of habit on usage behavior and behavioral intention to adopt BT in copywriter distribution platforms. In the era of SCM, SC professionals have to use BT in their daily operations due to its vital role in the SCM domain.…”
Section: Habitmentioning
confidence: 99%
See 1 more Smart Citation
“…While technophobia in the old continues to be extensively researched, e.g., [6,[13][14][15][16][17], some researchers have noted that the assumption of fear may be part of a stereotypical portrayal of the old, and thus a driver of ageism [18,19], and others have suggested that older individuals are not always more anxious or passive about technology than younger people [20][21][22]. Moreover, the literature does provide evidence of utilitarian reasons for adopting technology, such as its (perceived) usefulness or ease of use [23][24][25][26] which ipso facto are also reasons to reject technology. Perhaps even more interesting, and less researched, are what one may call ideological or value-based reasons to refuse technology.…”
Section: Refusal Of Technology As Rational Attitudementioning
confidence: 99%